Nanomagnetism and spintronics : fabrication, materials, characterization and applications - Nasirpouri, Farzad; Nogaret, Alain (World Scientific, 2011)
Spintronics manipulates individual magnetic moments to integrate logic functions and non-volatile information storage on the same platform. As is often the case in condensed matter science, advances are made through the synthesis of novel materials and high quality new physics materials. Giant magnetoresistance and dilute magnetic semiconductors are two such examples. However, the remarkable potential of spintronics for quantum computation faces major challenges when it comes to controlling simultaneously several qbits encoded in magnetic moments. After a brief introduction to concepts in nanomagnetism and spintronics, the text reviews recent techniques and their achievements in the synthesis and fabrication of magnetic nanostructures. The methods presented here emphasize bottom up or top down approaches for nanodots, nanowires and thin films. They include : focused ion beam irradiation, electron beam-induced chemical vapour deposition, chemical, and electrochemical methods. The later part of the book reviews magnetoelectric materials, the giant magnetoresistance in magnetic superlattices, dynamics effects in spin transfer torque oscillators, dilute magnetic oxides, rare earth nitrides with nuclear resonance scattering, and Mossbauer spectroscopy in spintronics. Finally, the last part of this book discusses applications to magnetic storage and bio-magnetism. Nanomagnetism and Spintronics will be useful to graduate students and researchers and engineers in the field of nanoscience.
Keywords: Spintronics.; Nanotechnology.; elektronické knihy; electronic books